Ananda Mitra. Television and Popular Culture in India. A Study of Mahbharat. Nueva Delhi, Thousand Oaks, Londres, Sage Publications, 1993. 196 pp. - Vernik, Esteban (Estudios de Asia y África, 1995)
-